Consumer Preferences On The Demand Of Duck Meat In The City of Ternate - Syafie, Yunus; Djumadil, Nurdiyanawati (Agrikan Jurnal Agribisnis Perikanan, 2022)
This study aimed to identify factors affecting consumer preferences for the demand of duck meat in Ternate city. Recently, the demand of duck meat has increased as indicated by the existence of restaurants or processed duck meat restaurants in Ternate city, which in turn leads to a competition between restaurant owners and or restaurants that sellduck meat processed product. Samples of duck meat processors were determined using the Cluster Sampling method, of which the samples were restaurants and restaurants that sell processed duck meat from3 areas in Ternae city (e.g., 3 restaurants in North Ternate, 10 restaurants in Central Ternate, and 3 restaurants in South Ternate). The data were analyzed using Conjoint analysis in SPSS ver. 24. The results showed that price factor influencing consumer preferences was at a moderate price level, that is IDR 50,000 with a positive usefulness value being 0.029, compared to the lowest price level being negative (-0.029), and the highest price being negative (-0.060). In the income factor affecting consumer preferences, there was the highest level of income, which was greater than IDR 3,000,000 with a positive usefulness value (0.918), and the second preference was at the income level of IDR 1,000,000 - IDR 300,000 with a positive utility value of 0.719, compared to the lowest income level which was negative (-0.918).